Muhammad Dawam Saleh's Thoughts on the Factors of Success in Education at Pondok Modern Darussalam Gontor - Rofi'i, Muhammad Arwani; Zahroh, Siti Fatimatuz (Journal of Pesantren and Diniyah Studies, 2024)
This research aims to analyze the key factors for the success of education at Gontor from the perspective of Muhammad Dawam Saleh. He is an alumnus of Pondok Gontor and the founder and leader of Pondok Pesantren Al-Ishlah Lamongan. This pesantren applies his analysis of the essence of Gontor's educational success. Additionally, he serves as a member of Gontor's Waqf Board. The research employs a qualitative method with a descriptive approach. Data was obtained through observation, interviews, and document studies. The results of the study reveal six essential foundations for Gontor's success. First, Gontor successfully implements a well-ordered boarding system, creating a conducive learning environment. Second, Gontor balances religious and general knowledge, providing comprehensive and relevant education. Third, the active use of Arabic and English broadens students' horizons. Fourth, strong discipline is applied in all areas of life, shaping resilient character. Fifth, extracurricular activities and leadership organizations provide valuable experiences for personal development. Sixth, the exemplary behavior of the Kiai in knowledge, practice, and worship serves as an inspiring example for students. An in-depth analysis of these six essences reveals the secret to Gontor's success in producing high-quality, integrity-driven youth. This research contributes to understanding effective and relevant educational strategies for addressing contemporary demands.